Analysis of Mining Subsidence Characteristics and Deformation Prediction considering Size Parameters and Mechanical Parameters. (22nd August 2022) - Liu, Shangguo; Li, Kaixin; Shi, Weiping; Wang, Zijun; Zhang, Haoran; Li, Zhaoying
Abstract : Crushing and caving of roof strata in goaf is an important factor affecting surface subsidence. In order to study the influence law of mining under thick loose layer, overburden size parameters, and initial mechanical parameters of collapse zone on surface subsidence, the law of surface subsidence was analyzed through measured data. On this basis, with the help of FLAC3D numerical simulation software, the surface subsidence was simulated by changing the above factors, and the evolution characteristics of the maximum surface subsidence under the influence of various factors were analyzed. Based on the grey relational analysis, the relational degree between each factor and the maximum surface subsidence value is analyzed, and through multiple nonlinear regression, the prediction model of mining subsidence deformation under thick loose layer considering the influence of seven factors is established. The results show that the mining thickness has the greatest influence on the surface subsidence, and cohesion has the least influence on surface subsidence. The rationality of the subsidence prediction model is verified by an example.